Chekhov’s Drama Context in Tanya-Tanya by Olga Mukhina - Pieczyński, Maciej (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
Contemporary Russian drama enters into a dialogue with literary tradition and in particular with the dramatic one. The works of the classics of modernism, including Anton Chekhov, very often become actualized in recent dramatic texts. For instance, Tanya-Tanya by Olga Mukhina refers to the artistic features of Chekhov’s ‘major plays’ and thus, in Natalya Fateyeva’s theoretical framework and terminology, Chekhov becomes a pre-text for Mukhina’s text. The general purpose of the paper is an intertextual analysis and interpretation of the latter play.